백서 교종 세포에서 레티노인산에 의한 카탈라제의 활성 증가가 방사선감수성에 미치는 효과 - 김화(Hua Jin), 전하연(Ha Yeun Jeon), 박우윤(Woo-Yoon Park), 김원동(Won-Dong Kim), 안희열(Hee-Yul Ahn), 유재란(Jae-Ran Yu) (Radiation oncology journal, 2005)
목 적: all-trans retinoic acid (ATRA)는 뇌종양 세포의 증식억제효과가 있으며, ATRA와 방사선의 병용은 악성 뇌종양의 치료 효과를 증진시키는 방법이 될 수 있다. 그러나 ATRA에 의해 항산화효소가 증가되며 이로 인해 방사선에 의해 생성된 reactive oxygen species (ROS)가 제거된다면 방사선의 효과는 낮아질 수 있다. 본 연구에서는 ATRA에 의해 유도되는 카탈라제(catalase)에 의한 방사선감수성의 변화를 보고자하였다. 대상 및 방법: 백서 교종세포(36B10)을 대상으로 ATRA 및 ATRA의 화학적 억제제인 3-amino-1, 2, 4-triazole (ATZ) 와 병용하여 카탈라제 활성도, 방사선감수성 및 ROS의 변화를 측정하였다. 카탈라제 활성도는 H2O2의 소멸을 자외선 분광광도계로 측정하는 방법을 이용해 정량하였으며, 방사선감수성은 단일집락군형성능력으로, ROS 는 2, 7-dichlorofluorescein diacetate 를 분광광도계로 측정하였다. 결 과: 카탈라제 활성도는 ATRA의 농도(10, 25, 50μM)에 따라 증가하였다. ATRA (10μM)와 방사선(4 Gy)의 병용에 의해 생존분획은 상승적(supra-additive)으로 감소하였으며, 이 감소된 생존분획은 ATZ 동시 투여에 의해 증가하였다. ATRA 10μM 또는 25μM을 48시간 처리 후 ROS는 대조군에 비해 각각 1.5배, 2배 증가하였고, 4 Gy와 ATRA의 병용군에서는 2.5배 증가하였다. ATRA와 방사선의 병용에 의해 증가된 ROS는 ATZ에 의해 감소되었다. 결 론: ATRA에 의해 유도되는 카탈라제는 방사선감수성을 감소시키지 않으며, 오히려 ROS의 증가에 의해 방사선감수성을 상승시켰다. 따라서 ATRA와 방사선의 병용은 뇌종양의 치료에 유용한 방법이 될 수 있을 것으로 보인다. Purpose: It has been reported that all-trans retinoic acid (ATRA) can inhibit glioma growing in vitro. However, clinical trials with ATRA alone in gliomas revealed modest results. ATRA has been shown to increase radiosensitivity in other tumor types, so combining radiation and ATRA would be one of alternatives to increase therapeutic efficacy in malignant gliomas. Thus, we intended to know the role of catalase, which is induced by ATRA, for radiosensitivity. If radiation-reduced reactive oxygen species (ROS) is removed by catalase, the effect of radiation will be reduced. Materials and Methods: A rat glioma cell line (36B10) was used for this study. The change of catalase activity and radiosensitivity by ATRA, with or without 3-amino-1, 2, 4-triazole (ATZ), a chemical inhibitor of catalase were measured. Catalase activity was measured by the decomposition of H2O2 spectrophotometrically. Radiosensitivity was measured with clonogenic assay. Also ROS was measured using a 2, 7-dichlorofluorescein diacetate spectrophotometrically. Results: When 36B10 cells were exposed to 10, 25 and 50μM of ATRA for 48 h, the expression of catalase activity were increased with increasing concentration and incubation time of ATRA. Catalase activity was decreased with increasing the concentration of AT (1, 10 mM) dose-dependently. ROS was increased with ATRA and it was augmented with the combination of ATRA and radiation. ATZ decreased ROS production and increased cell survival in combination of ATRA and radiation despite the reduction of catalase. Conclusion: The increase of ROS is one of the reasons for the increased radiosensitivity in combination with ATRA. The catalase that is induced by ATRA doesn`t decrease ROS production and radiosensitivity. KCI Citation Count: 0